Synthesis and X-ray single crystal structure of a cadmium(II) acetophenone thiosemicarbazone complex and its use as a single-source precursor for the preparation of CdS nanocrystallites and thin films - Palve, Anil M.; Joshi, Pranaya V.; Puranik, Vedavati G.; Garje, Shivram S. (Polyhedron, 2013)
{A cadmium(II) acetophenone thiosemicarbazone complex has been prepared and characterized by elemental analysis, infrared and nuclear magnetic resonance (H-1 and C-13H-1) spectroscopic techniques. Its single crystal structure has also been determined. The compound is found to be monoclinic, space group C2/c, with a = 12.1020(3) angstrom
Keywords: CdS; Nanocrystallites; Single source precursor; Thin films; Thiosemicarbazone complex